A History of the INTERNIST-1 and Quick Medical Reference (QMR) Computer-Assisted Diagnosis Projects, with Lessons Learned - Miller, R. A. (Yearbook of Medical Informatics, 2010)
The INTERNIST-1/Quick Medical Reference (QMR) diagnostic decision support project spans four decades, from 1971-onward. This paper describes the history of the project and details insights gained of relevance to the general clinical and informatics communities.
Keywords: Medical imaging; imaging informatics; PACS; image analysis workstations